A cross-sectional study on the relationship between intuitive eating, hedonic hunger and body mass index in university students - Öztürk Özkan, Gülin; Çetiner, Burku (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Unhealthy diet is an important factor in the formation of obesity. In recent years, the relationship between the concepts of intuitive eating and hedonic hunger and obesity has begun to be investigated. Objectives: The aim of this study is to evaluate the effects of intuitive eating and hedonic hunger on mental health, sleep quality and body mass index. Methods: In this cross-sectional study, a questionnaire including demographic and general health information, dietary habits, height and body weight measurements was administered to 62 female and 38 male university students aged 18-36 years. The questionnaire also included the Intuitive Eating Scale, the Food Power Scale, the Food Craving Questionnaire, the Pittsburg Sleep Quality Scale, the Warwick-Edinburgh Mental Well-Being Scale, and the Motivation to Eat Deliciously Scale. Number, percentage, mean and standard deviation values were calculated in the evaluation of the data. The relationships between variables were analyzed by independent samples T test, Pearson correlation and regression analyses. Results: A positive correlation was found between intuitive eating, hedonic hunger (r=0.332, p<0.01) and mental well-being (r=0.375, p<0.01). Intuitive eating was found to be negatively correlated with food cravings (r=-0.413, p<0.01) and body mass index (r=-0.202, p<0.05). It was found that 28.7% (R2 adjusted=0.287) of the variance of the intuitive eating score was explained by hedonic hunger, food craving and body mass index. Conclusions: Intuitive eating was associated with hedonic hunger, cravings, mental well-being, and body mass index. In addition, poor sleep quality supports hedonic hunger.